(untitled) (International Journal of Engineering and Computer Science, 2017)
Multi-hop wireless mesh networks (WMNs) experience frequent link failures caused by channel interference, dynamic obstacles, and/or applications’ bandwidth demands. These failures cause severe performance degradation in WMNs or require expensive manual network management for their real-time recovery. This paper presents an autonomous network reconfiguration system (ARS) that enables a multi-radio WMN to autonomously recover from local link failures to preserve network performance using a simplified approach. By using channel and radio diversities in WMNs, ARS generates necessary changes in local radio and channel assignments in order to recover from failures. Next, based on the thus-generated configuration changes, the system co-operatively reconfigures network settings among local mesh routers. The performance of ARS has been tested in a simulation platform (NS2) and comparison analysis is also done with the existing AODV protocol. An Enhanced ARS mechanism which suffers lesser delay than ARS mechanism is proposed and tested in a simulation platform